The Existence of Islamic Religious Education in Creating Quality Human Resources in Madrasah Aliyah - Musbaing Musbaing (P3I Luwu Raya, 2021)
Creating quality human resources in Madrasah Aliyah Pesantren al-Muhajirin, East Luwu Regency. The main issues raised are: How are the existence of Islamic education to create human resources in Madrasah Aliyah Pesantren al-Muhajirin and the extent to which Islamic education teaching methods are applied in Madrasah Aliyah Pesantren al-Muhajirin to create human resources quality. Therefore, this research uses several research methods, namely through population and sample methods, research instruments, inductive, deductive, and comparative thinking procedures and techniques. Based on the results of the study, it was found that the implementation of Islamic education in Madrasah Aliyah Pesantren Al-Muhajirin, plays an important role in the process of internalizing and understanding the values ​​of Islamic teachings to students, both understanding aspects of worship and morals, which are expected to be realized at the application level. With the existence of Islamic education to create quality human resources, students and educators should be aware that the ideal goal of education is to form humans who can combine faith, knowledge, and charity to create quality human resources (noble character). Moreover, have skills, especially the existence of PAI in Efforts to Create Quality Human Resources in Madrasah Aliyah Pesantren Al-Muhajirin. which is expected to materialize up to the application level. With the existence of Islamic education to create quality human resources, students and educators should be aware that the ideal goal of education is to form humans who can combine faith, knowledge, and charity to create quality human resources (noble character). Moreover, have skills, especially the existence of PAI in Efforts to Create Quality Human Resources in Madrasah Aliyah Pesantren Al-Muhajirin. which is expected to materialize up to the application level. With the existence of Islamic education to create quality human resources, students and educators should be aware that the ideal goal of education is to form humans who can combine faith, knowledge, and charity to create quality human resources (noble character). Moreover, have skills, especially the existence of PAI in Efforts to Create Quality Human Resources in Madrasah Aliyah Pesantren Al-Muhajirin.